Influence of age and comorbidity on prognosis and application of adjuvant chemotherapy in elderly Japanese patients with colorectal cancer: A retrospective multicentre study. (August 2017) - ,; Takemasa, I.; Hakamada, K.; Kameyama, H.; Takii, Y.; Hase, K.; Kotake, K.; Watanabe, T.; Takahashi, K.; Kanemitsu, Y.; Itabashi, M.; Yano, H.; et al.
Abstract: Background: Adjuvant therapy for colorectal cancer (CRC) in patients aged ≥75 years is supported by inadequate evidence, although such patients are increasing in number worldwide. Patients and methods: We assessed the influence of age and comorbidities on the prognosis of CRC in elderly patients using pooled data by the Japanese Study Group for Postoperative Follow-up of Colorectal Cancer. In total, 4598 patients (3304 with colon cancer and 1294 with rectal cancer) who underwent curative surgery from 2004 to 2006 were analysed with respect to age, Charlson comorbidity score (CS), tumour marker positivity, adjuvant therapy and prognosis. Results: The number of patients aged <64, 65–74 and >75 years was 2007 (44%), 1614 (35%) and 977 (21%), respectively. Tumour location, tumour marker positivity, clinical stage, performance of adjuvant therapy, CS and overall survival (OS) were significantly different among these age groups ( P  < 0.0001). Among patients aged ≥75 years with stage III CRC, 35% with colon cancer and 21% with rectal cancer received adjuvant therapy; these proportions were much lower than those in younger patients. Application of adjuvant therapy was dependent on the CS in patients aged ≤74 years, but not in older patients. Sex, the carcinoembryonic antigen concentration and adjuvant therapy were significantly associated with OS in elderly patients with stage III CRC. Conclusion: Age and comorbidities worsened the OS of patients with CRC who underwent curative surgery. However, patients aged ≥75 years were undertreated regardless of their CS despite the possibility of OS improvement by adjuvant therapy. Highlights: Age and comorbidities worsened the overall survival (OS) of colorectal cancer patients. The patients aged ≥75 were undertreated regardless of their Charlson score. Adjuvant therapy significantly improved OS of the patients aged ≥75.